2011
DOI: 10.1021/jp201794n
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Arginine Residues in Peptides by 2D-IR Echo Spectroscopy

Abstract: The CN stretching vibrations of the guanidyl group in the arginine dipeptide sidechain are examined by two-dimensional infrared spectroscopy. In D2O, the spectra display two distinct diagonal peaks. These nearly degenerate modes undergo ultrafast energy transfer. The energy transfer rate was determined directly from the 2D-IR spectra to be 1/2.1 ps-1. The cross peaks in 2D-IR arising from the energy transfer provide a definitive identification of arginine in larger proteins. An example of arginine in the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 41 publications
9
65
0
Order By: Relevance
“…At pH 7.0, in the closed state, both Ala30 and Gly34 in the drug free channel exhibit very slow spectral diffusion dynamics, indicating that the water structure near these sites is more ordered or even "frozen" on the timescale of our experiments, similar to that observed in ice crystals. 57 This is consistent with our prior experiments 33 and also MD simulations. 22,23 However, upon binding of a drug the water dynamics inside the channel become distinctively faster, as manifested by the faster spectral diffusion times of Al30 and Gly34.…”
Section: Probing Water Dynamics Through Amide Frequency Relaxationssupporting
confidence: 91%
See 3 more Smart Citations
“…At pH 7.0, in the closed state, both Ala30 and Gly34 in the drug free channel exhibit very slow spectral diffusion dynamics, indicating that the water structure near these sites is more ordered or even "frozen" on the timescale of our experiments, similar to that observed in ice crystals. 57 This is consistent with our prior experiments 33 and also MD simulations. 22,23 However, upon binding of a drug the water dynamics inside the channel become distinctively faster, as manifested by the faster spectral diffusion times of Al30 and Gly34.…”
Section: Probing Water Dynamics Through Amide Frequency Relaxationssupporting
confidence: 91%
“…A recent 2D IR study 33 has shown that energy transfer between two degenerate CN stretching modes of the guanidyl side chain of arginine, the infrared transitions of which overlap spectrally with isotopically edited amides, can occur on the timescale of a few picoseconds. Moreover, the carboxylate sidechains of glutamic and aspartic acids also absorb in the same spectral range as isotopically labeled amide modes.…”
Section: Mutation Of the M2 Sequencementioning
confidence: 99%
See 2 more Smart Citations
“…30 Here, these factors are assumed to only occur during the waiting time T. The S H T G n (ω, T) terms in Eq. (10) correspond to the individual Liouville pathway diagrams 30 such that,…”
Section: E Population Transfermentioning
confidence: 99%